Semi tandem base of support degrades both saccadic gaze control and postural stability particularly in older adults - Polastri, Paula F. [UNESP]; Barbieri, Fabio A. [UNESP]; Brito, Matheus B. [UNESP]; Bonfim, José V. A. [UNESP]; Gotardi, Gisele C. [UNESP]; Kuga, Gabriel K. [UNESP]; Rodrigues, Sérgio T. [UNESP] (Elsevier, 2019)
Differences in the postural stabilization of older and young adults have been shown to be task-dependent on both visual and postural challenges; however, the gaze behavior during such tasks has rarely been examined. This study investigated the effects of horizontal and vertical saccades on gaze control, center of pressure (CoP) and head displacement of young and older adults on different bases of support. Ten young adults (20.7 ± 3.4 years) and ten older adults (71.6 ± 3.1 years) remained in an upright stance on a force platform wearing an eye-head tracker device. The participants performed 30-second trials according to two bases of support (feet apart and semi-tandem) and three gaze behavior (fixation, horizontal and vertical saccades) conditions. Older adults presented greater CoP amplitude (p < 0.002) and velocity (p < 0.001) (ML axis), and higher head amplitude (ML) (p < 0.002) than young adults during the semi tandem base. Head displacement of both groups presented higher velocity (ML axis) during horizontal (p < 0.001) and vertical saccades (p < 0.01) than the fixation task only on the semi tandem base. There was higher number of fixations (p < 0.001) and lower mean fixation duration (p < 0.001) on the semi-tandem base (p < 0.05). The results showed higher gaze latency variability in vertical saccades for older adults (p < 0.01). Challenging postural tasks may alter postural adjustments and gaze control during saccadic tasks. Particularly, the greater postural instability of older adults increased the gaze latency variability during saccadic tasks, suggesting some deterioration in the posture-gaze relation with aging.
Keywords: Elderly; Eye movements; Postural control; Saccades; Semi tandem stance